New Anthology: Caucasus during the Mongol Period Overview: Overview - Sophia Vashalomidze; Aleksandre Tvaradze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
The anthology "Caucasus during the Mongol Period" (Dr. Ludwig Reichert Verlag in Wiesbaden, 2012: 360 pp.) takes a comparative approach to reconstructing the perceptions that the Armenians and Georgians developed of their Mongol conquerors in the 13th and 14th centuries. The focus lies on the perception of the historical outcomes of nomadic / sedentary interactions from the perspective of both the mundane and the clerical nobility. The Caucasus and its immediate sphere of influence as a whole will serve as the regional framework for our anthology. The broad scope of historical sequences regarding the Mongol conquest of Armenia and Georgia and the Mongol domination in and over Armenia and Georgia will be dealt with, whereby the local idiosyncrasies of these events are of particular interest.